2011
DOI: 10.1111/j.1600-0501.2011.02369.x
|View full text |Cite
|
Sign up to set email alerts
|

Conventional SLA and chemically modified SLA implants in patients with poorly controlled type 2 Diabetes mellitus – a randomized controlled trial

Abstract: Implant stabilization was similar for the conventional SLA and chemically modified SLA implants in type 2 diabetic patients with relatively poor glycemic control. Furthermore, this study demonstrated clinically successful implant placement even in poorly controlled diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 40 publications
4
67
0
5
Order By: Relevance
“…Magnetic RFA measurement revealed no signifi cant differences between both types of implants within the fi rst 16 weeks of integration. One SLA implant failed between week 4 and 6 [ 171 ]. These results again suggest that, when used in compromised patients, mod-SLA implants show a very high predictability of success and signifi cantly less crestal bone loss in short-term healing compared to SLA implants, which also successfully integrate.…”
Section: Modsla: On Cp Ti Tissue-level Implantsmentioning
confidence: 60%
See 2 more Smart Citations
“…Magnetic RFA measurement revealed no signifi cant differences between both types of implants within the fi rst 16 weeks of integration. One SLA implant failed between week 4 and 6 [ 171 ]. These results again suggest that, when used in compromised patients, mod-SLA implants show a very high predictability of success and signifi cantly less crestal bone loss in short-term healing compared to SLA implants, which also successfully integrate.…”
Section: Modsla: On Cp Ti Tissue-level Implantsmentioning
confidence: 60%
“…Further studies confi rmed signifi cantly increased RFA values for modSLA implants compared to SLA in investigations when implants were placed in mandibles and when RFA was performed electronically [ 169 ]. In additional studies, no signifi cant ISQ differences between both types of implants were detected when RFA was performed magnetically (Osstell mentor ®, Integration Diagnostics AB, Gothenburg, Sweden) [ 169 -171 ] or when both implants were compared in diabetic patients [ 171 ]. For implants placed in the maxilla, only palatal-inserted orthodontic implants (Orthosystem ® , Institut Straumann AG, Basel, Switzerland) with a modSLA surface showed signifi cantly increased ISQ values after 12 weeks of healing compared to SLA implants (electronic RFA).…”
Section: Modsla: On Cp Ti Tissue-level Implantsmentioning
confidence: 95%
See 1 more Smart Citation
“…Conversely, the other diabetics, with better glycaemic control, did not exhibit these complications. However, Khandelwal et al 31 recently reported clinical success for 47 of 48 study implants in diabetic patients with HbA1c levels ranging from 7.0% to 12.5% over a short-term follow-up (4 months).…”
Section: Discussionmentioning
confidence: 95%
“…Имеются данные, что неспособность к остеоинтеграции в начальной фазе установки имплантатов приводит к фиброзной инкапсуляции имплантата и подвижности, что в конечном счете приводит к отторжению имплантата [4]. Большая часть представлений о процессе интеграции дентальных имплантатов происходит от исследований на экспериментальных моделях на животных, при этом в большинстве экспериментов использована модель сахарного диабета 1 типа (СД1) на грызунах, однако патофизиология СД1 отличается от СД2, частота которого растет при старении взрослого населения.…”
unclassified